2005
DOI: 10.1115/1.2033903
|View full text |Cite
|
Sign up to set email alerts
|

Natural Convection Patterns in Right-Angled Triangular Cavities with Heated Vertical Sides and Cooled Hypotenuses

Abstract: The present investigation deals with the numerical computation of laminar natural convection in a gamma of right-angled triangular cavities filled with air. The vertical walls are heated and the inclined walls are cooled while the upper connecting walls are insulated from the ambient air. The defining apex angle α is located at the lower vertex formed between the vertical and inclined walls. This unique kind of cavity may find application in the miniaturization of electronic packaging severely constrained by s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…Natural convection in triangular enclosures has been a subject of interest in many research studies because of its applicability in various fields such as air-filled attic spaces of sloped-roof-buildings [1,2], roof type solar stills [3], triangular shaped solar collectors [4e6] and miniaturised electronic components [7,8]. For the first time, Flack et al [9] experimentally studied natural convection in an isosceles air-filled triangular enclosure with two isothermal walls and an insulated bottom.…”
Section: Introductionmentioning
confidence: 99%
“…Natural convection in triangular enclosures has been a subject of interest in many research studies because of its applicability in various fields such as air-filled attic spaces of sloped-roof-buildings [1,2], roof type solar stills [3], triangular shaped solar collectors [4e6] and miniaturised electronic components [7,8]. For the first time, Flack et al [9] experimentally studied natural convection in an isosceles air-filled triangular enclosure with two isothermal walls and an insulated bottom.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the average Nusselt number for 4 ¼ 15 cavities is found be higher in all the cases, followed by30 and 45 cavities, respectively. It is interesting to note that, Nu l and Nu r increase with increase in Ra for 4 ¼ 30 and 45 in all cases.…”
mentioning
confidence: 88%
“…Kent [29] analyzed natural convection within isosceles triangle with base angle varying from 15 to 75 and observed that the enclosures with a low aspect ratio have higher heat transfer rates from the bottom surface of the triangular enclosure. Ridouane et al [30] investigated convection in right-angled triangular cavities with apex angles 5 e63 . Varol et al [31] reported the studies on free convection in right-angle triangular enclosures filled with porous media.…”
Section: Introductionmentioning
confidence: 99%
“…The lower aspect ratio has high heat transfer rate from the bottom surface of the triangular enclosure. Ridouane et al (2005) have numerically computed laminar natural convection in a right-angled triangular cavity filled with air. The vertical side wall is considered as hot wall while cooling is done from hypotenuse of the triangular enclosure.…”
Section: Introductionmentioning
confidence: 99%